2018
DOI: 10.1002/adfm.201706230
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Induced Multilevel Current Amplification Memory Effect in Zinc Oxide Rods Resistive Switching Devices

Abstract: Zinc oxide (ZnO) devices represent an alternative in the semiconductor technology for their application in resistive switching memory devices and ultraviolet (UV) photodetectors due to their chemical and electrical properties. The multilevel current amplification of ZnO rods RRAM devices induced by UV light illumination is reported here for the first time. The resistive switching mechanism underlying in this type of devices is attributed to the formation of conductive filaments composed of oxygen vacancies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 60 publications
0
49
0
1
Order By: Relevance
“…Enhanced photoconductivity properties compared to bulk materials or thin films can be observed in nanostructures, since a larger harvesting activity of photons and surface state densities are correlated with the high surface to volume ratio of these structures. An increase of resistive switching performances in terms of endurance has been reported also in ZnO NR arrays contacted by Ag and FTO electrodes by Russo et al [294] Instead, an opposite trend was reported by Bera et al [292] that observed a suppression of resistive switching characteristics as a consequence of UV illumination in ZnO NRs/Nb-doped SrTiO 3 heterojunctions. In this case, authors pointed out that the illumination conditions (with a xenon light source, spectrum in the range 200-2500 nm) can strongly modify the I-V characteristic inducing resistive switching.…”
Section: Light-modulated Resistive Switchingmentioning
confidence: 78%
“…Enhanced photoconductivity properties compared to bulk materials or thin films can be observed in nanostructures, since a larger harvesting activity of photons and surface state densities are correlated with the high surface to volume ratio of these structures. An increase of resistive switching performances in terms of endurance has been reported also in ZnO NR arrays contacted by Ag and FTO electrodes by Russo et al [294] Instead, an opposite trend was reported by Bera et al [292] that observed a suppression of resistive switching characteristics as a consequence of UV illumination in ZnO NRs/Nb-doped SrTiO 3 heterojunctions. In this case, authors pointed out that the illumination conditions (with a xenon light source, spectrum in the range 200-2500 nm) can strongly modify the I-V characteristic inducing resistive switching.…”
Section: Light-modulated Resistive Switchingmentioning
confidence: 78%
“…The fundamental processes behind the observed experimental results are related to strain‐induced polarization charges, which in turn can effectively modulate the oxygen absorption/desorption process, resulting in tunable optoelectronic performance . In fact, multilevel photo current amplification with UV illumination in ZnO‐based device has been demonstrated due to oxygen absorption/desorption process by Russo et al For better understanding, the band diagram of the device under the thermal equilibrium condition is presented in Figure d …”
mentioning
confidence: 96%
“…As strain changes from the compressive to the tensile, it is found that the current decreases, as also occurs with illuminating intensities. This indicates that the current across the device can be modulated over a wide range by applying strain as well as UV intensity, offering multilevel operation . A comprehensive map of photocurrent values was obtained by tuning of the UV intensities and the mechanical strain, as shown in Figure c.…”
mentioning
confidence: 99%
See 2 more Smart Citations